Health and safe behavior of traditional market traders in minimizing the risk of Covid-19 in Pontianak - Elly Trisnawati; Maria Yolan Sukemi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background : Implementation of health protocols must pay attention to the point of transmission of Covid-19. The market is an active place every day. This study measures the implementation of healthy and safe behavior by market traders as assessed by 2 main indicators, namely implementation of health protocols and participation in the Covid-19 vaccination. The results of initial observations made by researchers showed that as many as 30% of market traders wore masks during their activities in the market, most traders did not apply physical distancing. As many as 45% of traders who have just joined the vaccination program. This study aims to identify factors related to the healthy and safe behavior of traditional market traders in Pontianak. Method : The design of this research is analytic observational with cross sectional approach. The sample in this study were 105 traditional market traders in 7 selected markets. Samples were taken through accidental sampling technique. Research data was collected using the KoboCollect application. Research outputs will be published in Sinta accredited journals as a form of dissemination of research results. Results : The data shows that the factors associated with the healthy and safe behavior of traditional market traders are knowledge, attitude, availability of hand washing facilities, workplace social support, availability of educational media in the market. While the factors of age, gender, education, income and family support are not factors related to the healthy and safe behavior of traditional market traders in Pontianak. Conclusion : It is hoped that the results of this research can be additional support for the policy of implementing health protocols in the market and increasing awareness of market traders in increasing healthy and safe behavior while working and following complete vaccinations because Covid-19 has not completely ended.